Tales of a Flow Stayed By Nothing: Menstruation in Immigration Detention - Johnson, Kit (Columbia Journal of Gender and Law, 2021)
When Fauziya Kassindja landed at New York’s JFK airport in 1994, she was seventeen, seeking asylum, and fleeing the brutal practice of female genital mutilation. She was also menstruating. Hours after her arrival, Fauziya was strip searched, forced to stand before a female officer “completely naked, soiled pad exposed, shamed beyond words.” She was then transferred to an off-site detention facility where she was strip- searched again. When Fauziya asked where she should place her soiled pad, the female guard responded: “I don’t know. Why don’t you eat it?” When Fauziya asked for a new pad, she was told she could ask for one the next morning. She was given absolutely nothing to stay her flow—not even toilet paper or paper towels. This was the beginning of Fauziya’s experience with immigration detention. She would remain there for sixteen months.